2020
DOI: 10.3389/fncel.2020.00097
|View full text |Cite
|
Sign up to set email alerts
|

Blocking the LncRNA MALAT1/miR-224-5p/NLRP3 Axis Inhibits the Hippocampal Inflammatory Response in T2DM With OSA

Abstract: Studies have shown that diabetes can cause cognitive dysfunction, and cognitive dysfunction in patients with diabetes combined with obstructive sleep apnea (OSA) is more severe. LncRNAs are known to be associated with type 2 diabetes mellitus (T2DM) with OSA. This study aimed to investigate the role and underlying mechanism of the lncRNA MALAT1/miR-224-5p/NLRP3 axis in T2DM with OSA. qRT-PCR was used to quantify the expression of MALAT1, miR-224-5p, and NLRP3 in brain tissues. NLRP3 expression was assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“… 50 , 51 Overexpression of miR-224-5p can significantly inhibit the expression of TNF-α and IL-1β in the hippocampus following onset of type 2 diabetes mellitus in association with obstructive sleep apnea. 52 Moreover, miR-224 suppresses airway epithelial cell inflammation in PM2.5-induced asthmatic mice due to its ability in reducing the expression of pro-inflammatory mediators transforming growth factor-β (TGF-β), MMP9, TIMP-1, and RORγt. 53 These reports highlighted the protection from inflammation conferred by miR-224.…”
Section: Discussionmentioning
confidence: 99%
“… 50 , 51 Overexpression of miR-224-5p can significantly inhibit the expression of TNF-α and IL-1β in the hippocampus following onset of type 2 diabetes mellitus in association with obstructive sleep apnea. 52 Moreover, miR-224 suppresses airway epithelial cell inflammation in PM2.5-induced asthmatic mice due to its ability in reducing the expression of pro-inflammatory mediators transforming growth factor-β (TGF-β), MMP9, TIMP-1, and RORγt. 53 These reports highlighted the protection from inflammation conferred by miR-224.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we demonstrated that CD27-AS1 promoted AML progression through targeting miR-224-5p. Aside from CD27-AS1, miR-224-5p was indeed regulated by multiple lncRNAs, such as LncRNA MALAT1 34 and NEAT1 35 in other human diseases. MALAT1 promoted the malignant phenotype of AML cells 36 , whereas lncRNA NEAT1 inhibited the development of AML 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Zhu[36] found that LINC00094 inhibited endotoxin-1 expression by up-regulating miR-224-4p/miR-497-5p, promoted the expression of ZO-1, Okrudin and Claudine-5, and nally alleviated BBB Permeability in the AD microenvironment. Du [37] found that MiR-224-5p can reduce the activation of microglial in ammation by regulating the expression of NLRP3. Liu[38] found that miR-224-5p plays a vital role in hypoxic neuronal injury through NR4A1, which may be an important regulatory mechanism of neuronal OGD injury.…”
Section: Discussionmentioning
confidence: 99%